Le modèle des parcs nationaux à l’épreuve du territoire - Nicolas Alban; Gilles Hubert (VertigO)
The national Park model which was set up in 1960 by French Government failed to find its place on the territory, because of its top-down and too statutory process. Despite of this failure and quick political and scientific changes, French Government took time to suggest a reform for the system. It came finally in 2006. But hesitations from Parliament members lead to a "no-choice" and decision-making responsibility was given up to administration. As a result, directions from national Park organizations are under stress, torn between several governance scenes and conflicting choices. At least, this situation could call into question French national Park system. In that way, national Park organizations need to prove they are able to increase in value the territory. Otherwise, they could be disqualified by local stake-holders. So they have to build a new legitimacy, by using local opportunities.